tell me the answers
Attachments:
![](https://hi-static.z-dn.net/files/d4c/4c44218cfb070cbd82fa20ade1dba499.jpg)
Answers
Answered by
1
(c) is the answer for the question
Answered by
8
ans = 1/6
proof =
tan inverse 2x + tan inverse 3x = π/4
tan (tan inverse 2x + tan inverse 3 x ) = π/4
2x+3x / 1-2x+3x
![6x ^{2} + 5x ^{2} - 1 = 0 6x ^{2} + 5x ^{2} - 1 = 0](https://tex.z-dn.net/?f=6x+%5E%7B2%7D+%2B+5x+%5E%7B2%7D+-+1+%3D+0)
- 5 + - √25 + 24 / 12 = -1 or 1/6
Hope this helps you dude all the best dude
and be brainlist dude ✌️✌️✌️✌️✌️
proof =
tan inverse 2x + tan inverse 3x = π/4
tan (tan inverse 2x + tan inverse 3 x ) = π/4
2x+3x / 1-2x+3x
- 5 + - √25 + 24 / 12 = -1 or 1/6
Hope this helps you dude all the best dude
and be brainlist dude ✌️✌️✌️✌️✌️
chodeswamyakhilesh:
thankyou
Similar questions